2019
DOI: 10.1186/s12905-019-0752-z
|View full text |Cite
|
Sign up to set email alerts
|

Age-specific values of Access anti-Müllerian hormone immunoassay carried out on Japanese patients with infertility: a retrospective large-scale study

Abstract: Background The ovarian reserve in women is known to correlate with anti-Müllerian hormone (AMH) levels, and currently the latest, third-generation, fully-automated AMH immunoassays, such as Access and Cobas, are beginning to be used for measuring AMH levels. However, the age-specific reference values obtained for AMH levels have been based on samples from an American population, measured using first-generation immunoassays. In this study, we attempted to determine the age-specific AMH reference va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 31 publications
1
12
1
Order By: Relevance
“…Considering the possible variations due to the different assays used [serum AMH concentrations seem to be 20% lower when Elecsys is compared with conventional AMH Gen II assays (41)], AMH values for Chinese ethnicity seem clearly higher than for the Arab population. Compared to Japanese population, the median AMH values presented in this study are 38.4% lower using Access assay (14). This percentage is far from the 10% expected due to the different assays used (42).…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…Considering the possible variations due to the different assays used [serum AMH concentrations seem to be 20% lower when Elecsys is compared with conventional AMH Gen II assays (41)], AMH values for Chinese ethnicity seem clearly higher than for the Arab population. Compared to Japanese population, the median AMH values presented in this study are 38.4% lower using Access assay (14). This percentage is far from the 10% expected due to the different assays used (42).…”
Section: Discussioncontrasting
confidence: 73%
“…AMH ranges over the life span of a women were published by Kelsey et al (11) by combining data from 20 studies (3260 data points). Likewise, most studies have evaluated the ovarian reserve parameters in Caucasian populations and only few publications have considered other ethnicities (12)(13)(14). However, it has been shown that AMH and AFC varies across different age-matched ethnic populations (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many other studies have reported an inverse correlation between age and AMH levels. [ 15 16 17 18 ] Interestingly, the decrease in median AMH with age observed in Groups A and B was faster as compared to Group C. This indicates that Indian women, whether seeking infertility treatment or with history of natural conception, experience a faster decline in AMH as compared to their healthy Caucasian counterparts. This trend was observed starting at a young age and continues consistently throughout the studied age groups.…”
Section: Discussionmentioning
confidence: 94%
“…However, it is helpful to minimize the mixed effect of age on the association between low AMH level and pregnancy outcome following IVR treatment. In addition, the third-generation automated AMH assay was employed for the measures in the present study [ 26 ]. Several studies show that the automated AMH assay is more sensitive than the Gen-II ELISA kit [ 27 ].…”
Section: Discussionmentioning
confidence: 99%